The Role of Online Platforms in Addressing Gender Based Violence in Wagige Kiambu County, Kenya - Sele, John Philip; Whittaker, Tee Jay (African Journal of Stability and Development (AJSD), 2025)
Gender-based violence (GBV) remains a critical global issue, disproportionately affecting women, men, and marginalised communities. As digital technologies evolve, online platforms such as Facebook, YouTube, TikTok, forums, and specialised support websites have emerged as key tools in addressing GBV. This study examines the role of these platforms in raising awareness, providing resources, facilitating reporting, and mobilising communities to combat GBV in Wagige, Kiambu County, Kenya. The research explores three main questions: (i) How effective are online platforms in raising awareness and providing resources compared to traditional support systems? (ii) What mechanisms do online platforms use to facilitate reporting and support for victims, and how do these impact victims’ willingness to seek help? (iii) How do online platforms contribute to the mobilisation of communities and advocacy groups, and what role does user engagement play? Data were collected through a questionnaire from 20 respondents, to capture their experiences with online platforms addressing GBV. Findings suggest that 85% of respondents were aware of online platforms dedicated to GBV, with 60% having accessed resources. While 90% of respondents found these platforms somewhat or very effective compared to traditional systems, challenges such as difficulty navigating reporting mechanisms and limited trust were also noted. Additionally, 50% of the respondents participated in online discussions on GBV, demonstrating the potential for community mobilisation on these platforms. However, user engagement was seen as key, with respondents stating that advocacy efforts are more successful when users actively participate in campaigns and discussions. The study observes that even as online platforms enhance awareness and support for GBV manifold, barriers persist in access, usability, and community mobilisation. The report also includes recommendations on how the mechanisms of reporting, preserving anonymity, and encouraging users to more actively use the platforms can be improved to increase their impact on GBV.